Desenvolvimento de blendas de PLA e polímeros do glicerol e nanocompósitos com nanowhiskers de celulose - Silva, Amanda Vieira da (2018)
Biodegradable polymers have been widely studied due to the social quest to reduce the dependence of fossil products. Poly(lactic acid) - PLA is highlighted because it is biodegradable and has a high modulus of elasticity and stiffness, however low thermal stability, flexibility and impact resistance that limit its use. In this work, blends with PLA and glycerol polymers, and nanocomposites with cellulose nanowhiskers (CNW) were prepared to evaluate the blending effect and nanocomposite formation on the thermal and mechanical properties of PLA. Glycerol polymers based on maleic anhydride and adipic acid were synthesized to generate poly(glycerol maleate) - PGM, poly (glycerol adipate) - PGA and the copolymer poly (glycerol maleate - co - adipate). These polymers were added to PLA at concentrations of 2.5%, 5% and 10 wt.%. In addition, cellulose nanowhiskers were extracted by acid hydrolysis and added at 3 wt.% to blends containing 5% glycerol polymer. Samples were mixed in an internal mixer , then milled and injected. The blends and nanocomposites were characterized by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), tensile tests and scanning electron microscopy (SEM). Thermal analysis indicated that there was a decrease in the degradation temperature of the samples, even for the nanocomposites, and there was formation of a second phase with greater crystalline organization and higher porosity. Porosity and processing conditions affected the mechanical properties, and it was only possible to observe that the presence of NWC in PLA allowed a slight deformation. In general, the different injection temperatures as well as the formation of blends with glycerol polymers are a way of compatibilizing PLA and CNW. Despite our results not being satisfactory in terms of mechanical properties, they encourage the pursuit for the development of new biidegradable materials.